P207 A rare case of disseminated Blastomycosis in an immunocompetent host: A report from North India. (20th September 2022) - Gupta, Bishal; Marak, Rungmei S.K.; Kaul, Anupama; Dubey, Akanksha; Dixit, Ajai Kumar
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM:   Objectives: Blastomycosis is a serious life-threatening systemic infection caused by dimorphic fungi Blastomyces dermatitidis. Infection is acquired via inhalation of airborne conidia or traumatic inoculation. It may produce a spectrum of infections ranging from asymptomatic infections in immunocompetent patients to disseminated disease, including skin, bone, genitourinary tract, and central nervous system (CNS) involvement in immunocompromised patients. This fungal infection is very rare in India. We report a unique case of disseminated blastomycosis in an immunocompetent patient. Methods: A 37-year-old male patient from Kanpur, Uttar Pradesh presented with chief complaints of hematuria associated with passage of blood clots for 3 months. There was no history of dysuria, fever, or pain abdomen. When he was evaluated for gross hematuria, his USG abdomen was suggestive of bilateral renal masses. To rule out bilateral renal cell carcinoma an FDG pet scan was done which was suggestive of FDG avid lesions in the bilateral kidneys. He also had enlarged left supraclavicular and left cervical lymph nodes. Multiple nodular and verrucous lesions were seen all over the face. He complained of pain in the left ankle; with a small wound opening on the medial malleolus of the left ankle. Results: A skin biopsy was taken from one of the nodular and verrucous lesions over face. A total of 10% wet mount KOH preparation shows no epithelial cells, plenty of pus cells, no RBCs, and plenty of thick-walled round yeasts and some with broad-based budding yeasts (8-12 microns) suggestive of Blastomyces species. Renal abscess pus FNAC, left cervical lymph node, and CT-guided biopsy from the medial malleolus of the left ankle also showed similar round yeasts and some with broad-based budding suggestive of Blastomyces species. Hence, a preliminary diagnosis of disseminated blastomycosis was made. Cultures were put in SDA at 25°C and 37°C and after a week, colonies appeared as fluffy white glabrous with reverse cream-colored non-sporulating colony. On day 25, colony appears as tan glabrous fluffy with brownish reverse with sporulation. LPCB was done from the colony which showed thin septate hyphae with pedunculated and sessile spherical to pyriform and smooth walled microconidia suggestive of Blastomyces dermatitidis. He was started on IV liposomal amphotericin B for 20 days. HCV RNA was detected incidentally and he had transaminitis therefore, he could not be started on itraconazole, he was started on fluconazole. His facial lesions cleared dramatically; his left ankle pain and swelling had resolved. At present, he was symptomatically better and was discharged on 200 mg fluconazole once daily and advised for follow-up after 2 weeks. Conclusion: Blastomycosis is a relatively uncommon geographically restricted chronic granulomatous disease that mainly occurs in the endemic regions. This fungus lives primarily in moist soil and decomposing matter, and inhabits the mid-west, south-central, southeastern United States as well as the boreal forests of Ontario and Quebec in Canada. Very little is known about the natural habitat and environmental distribution of Blastomyces species in India. This case is unique because the patient is immunocompetent and has no history of travel outside of India.